Changes in nursing students' knowledge, attitudes and interest in caring for older adults: A longitudinal cohort study. (March 2020) - McCloskey, Rose; Yetman, Lynda; Stewart, Connie; Slayter, Jeremy; Jarrett, Pamela; McCollum, Alexander; Stoica, George
Abstract: Nursing education programs have a responsibility to prepare future nurses to care for the growing number of older adults who will be accessing health care services. Preparation involves ensuring students have the knowledge, skills and desire to provide quality care to older adults. A longitudinal cohort study was conducted to collect data on students' knowledge of, attitudes towards, and interest in working with older adults during each year of an undergraduate nursing program. Data were collected using the Kogan Attitudes Towards Older People Scale, Palmore's Fact on Aging Quiz and a demographic instrument designed specifically for this study. Results showed slight improvements in students' overall attitudes towards older adults at the completion of their nursing degree. Increases in knowledge were seen in 12 of 24 areas measured. Gerontology as a preferred career choice was highest immediately following a clinical placement focusing on caring for older adults. Integrating gerontological clinical experiences into a beginning fundamental nursing course does not necessarily improve students' learning in the area of caring for older adults. Nursing programs have a responsibility to design, monitor and update curricula to ensure students are being adequately prepared to care for older adults. Highlights: It is important that future nurses have knowledge and interest in caring for older adults. Gerontology is not a popular career preference amongst nursing students. Interest in gerontology is linked with clinical experiences. Ongoing evaluation of nursing curricula is important.